PENDEKATAN AL-MAṢLAḤAH DALAM FATWA MAJELIS ULAMA INDONESIA (MUI) NOMOR 24 TAHUN 2017 TENTANG HUKUM DAN PEDOMAN BERMUAMALAH MELALUI MEDIA SOSIAL - Ikhwanuddin Harahap (Institut agama islam negeri Padangsidimpuan, 2017)
Al-maslahah is one of the considerations for the Indonesian Ulema Council (MUI) in determining the MUI fatwa No. 24 of 2017 on Law and Guidance Bermuamalah through Social Media. Thus, the Indonesian Ulema Council (MUI) sees that digital media based on social media has great benefit and goodness for human beings. The benefit and goodness of man himself is the purpose of establishing the Shari'a (maqāṣid al-syar'ah). Thus, social media-based digital media are in line with maqāṣid al-syar'ah. Therefore, digital media-based social media must be managed and developed in order to be able to meet the needs of modern society today. Although digital media based on social media also has weaknesses. If social media-based digital media is abused, then social media-based digital media can bring destruction, harm and even misfortune (mafsadat) to mankind. It is in this context that this fatwa is present. This fatwa is expected to guard the values of goodness and goodness inherent in digital media based on social media. In other words, this fatwa gives signs how to use digital media based on social media properly and correctly, so that it is not misused by mankind.